2020
DOI: 10.1098/rsbl.2019.0940
|View full text |Cite
|
Sign up to set email alerts
|

Change in geomagnetic field intensity alters migration-associated traits in a migratory insect

Abstract: Geomagnetic field (GMF) intensity can be used by some animals to determine their position during migration. However, its role, if any, in mediating other migration-related phenotypes remains largely unknown. Here, we simulated variation in GMF intensity between two locations along the migration route of a nocturnal insect migrant, the brown planthopper Nilaparvata lugens , that varied by approximately 5 µT in field intensity. After one generation of exposure, we tested for changes in ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Previous studies revealed that exposure of both small brown planthopper and brown planthopper to NZMF delayed egg and nymphal developmental durations and decreased adult weight and female fecundity of insects ( Wan et al, 2014 , 2021 ). In addition to growth and development, the NZMF also affected positive phototaxis and flight capacity of the white-backed planthopper Sogatella furcifera ( Wan et al, 2016 , 2020 ). Exposure to enhanced GMF also reduced the phototaxis of N. lugens ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that exposure of both small brown planthopper and brown planthopper to NZMF delayed egg and nymphal developmental durations and decreased adult weight and female fecundity of insects ( Wan et al, 2014 , 2021 ). In addition to growth and development, the NZMF also affected positive phototaxis and flight capacity of the white-backed planthopper Sogatella furcifera ( Wan et al, 2016 , 2020 ). Exposure to enhanced GMF also reduced the phototaxis of N. lugens ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The brown planthopper, N. lugens , is one of the most important rice pests in Asia, which has the ability of magnetic response due to the magnetic particles in its abdomen (Chapman et al ., 2011; Xie et al ., 2011; Yan et al ., 2015; Pan et al ., 2016; Wan et al ., 2020, 2021). Recently, research based on the physiological magnetic response of N. lugens found that the deletion of the magnetic receptor protein (MagR/IscA1) significantly shortened the life span of brachypterous female adults, providing a new strategy for the control of N. lugens (He et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, in order to explore the physiological functions of MagR (IscA1) in insects, the rice brown planthopper ( Nilaparvata lugens ) was selected as a model insect because of its special feeding habit and magnetic response ability due to the magnetic particles in its abdomen (Chapman et al ., 2011; Xie et al ., 2011; Yan et al ., 2015; Pan et al ., 2016; Wan et al ., 2020, 2021). The target gene, MagR ( NlMagR ), was silenced by using RNAi in the brachypterous female adults of N. lugens to investigate the effect of NlMagR on insect reproduction via measuring their fecundity and hatchability.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression analyses have provided insight into the complex regulatory architecture underlying HMF-triggered bioeffects ( Xu et al, 2012 ; Fedele et al, 2014a ; Mo et al, 2014 ; Wan et al, 2014 ; Wan et al, 2015 ; Bae et al, 2016 ; Fu et al, 2016 ; Mo et al, 2016 ; Wan et al, 2016 ; Agliassa et al, 2018 ; Agliassa and Maffei, 2019 ; Zhang B. et al, 2021 ; Yan et al, 2021 ) and magnetoreception ( Yoshii et al, 2009 ; Gegear et al, 2010 ; Xu et al, 2012 ; Fedele et al, 2014a ; Fedele et al, 2014b ; Mo et al, 2014 ; Wan et al, 2014 ; Wan et al, 2015 ; Bae et al, 2016 ; Bazalova et al, 2016 ; Fu et al, 2016 ; Mo et al, 2016 ; Wan et al, 2016 ; Fitak et al, 2017 ; Agliassa et al, 2018 ; Gunther et al, 2018 ; Wang et al, 2018 ; Agliassa and Maffei, 2019 ; Wan et al, 2020a ; Hochstoeger et al, 2020 ; Zhang B. et al, 2021 ; Gao et al, 2021 ; Wan et al, 2021 ; Yan et al, 2021 ). Reverse transcription quantitative polymerase chain reaction (RT-qPCR) is a powerful tool commonly employed to detect mRNA transcription levels ( Derveaux et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled variation in detected mRNA amounts can arise due to many factors including tissue type, sampling protocol, total RNA extraction and reverse-transcription efficacy, with unreliable RGs leading to poor reproducibility in genetic and gene expression studies of magnetobiology ( Ponton et al, 2011 ). Insects, with relatively short generation times and powerful molecular toolboxes [e.g., fruit fly ( Gegear et al, 2008 ; Yoshii et al, 2009 ; Gegear et al, 2010 ; Foley et al, 2011 ; Fedele et al, 2014a ; Fedele et al, 2014b ), monarch butterfly ( Gegear et al, 2010 ; Wan et al, 2021 ), termite ( Gao et al, 2021 ), cockroach ( Bazalova et al, 2016 ), firebug ( Netusil et al, 2021 ), rice planthopper ( Wan et al, 2014 ; Wan et al, 2015 ; Wan et al, 2016 ; Wan et al, 2020a ; Zhang Y. et al, 2020 ; Wan et al, 2020b )] , provide excellent models for studying the gene regulatory networks mediating biological responses to changes in magnetic field intensity or direction. However, studies assessing the stability of RGs prior to conducting gene expression analyses in insect magnetobiology studies are rare ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%